1998
DOI: 10.1159/000012714
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Human Milk Produced by Women Consuming a Maize-Predominant Diet Typical of Rural Mexico

Abstract: The milk composition of women on a typical rural Mexican diet was compared with that secreted by American women, consuming a diet typical of affluent countries. Milk concentrations of free fatty acids, cholesterol, total amino acids, and selected key minerals were analyzed at 4 or 6 months postpartum. The total milk fat concentration was lower in the Otomi (22.7 ± 6.7 mg/g milk) than in the American women (31.3 ± 5.4 mg/g milk, p = 0.001). Although the absolute concentration did not differ, cholesterol, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The lauric and myristic acid levels of milk in the group consuming the fat-free diet were much higher than levels in women consuming the fatcontaining diet. Studies of milk composition from women whose typical diet was low in fat agree with our finding that lauric and myristic acid levels are elevated (19,28,29).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The lauric and myristic acid levels of milk in the group consuming the fat-free diet were much higher than levels in women consuming the fatcontaining diet. Studies of milk composition from women whose typical diet was low in fat agree with our finding that lauric and myristic acid levels are elevated (19,28,29).…”
Section: Discussionsupporting
confidence: 86%
“…Parallels can be seen between the levels of several milk FA and maternal diets. For example, our data demonstrated that milk LA levels were relatively high in countries typically consuming a high-maize diet, such as Mexico (19) and Chile (20). The Philippines presented an unusual profile, with low LA levels and high levels of lauric and myristic acids, most likely indicating consumption of diets limited in both essential FA and total fat.…”
Section: Discussionmentioning
confidence: 70%
“…Mean breast milk DHA concentrations in our study population are similar to those seen in women in the US and other countries where dietary DHA consumption is lower than recommended (16,18). A study of Otomi women living in rural Mexico found a lower concentration of ALA, a similar concentration of AA, and a higher concentration of LA in breast milk (32).…”
Section: Discussionsupporting
confidence: 78%
“…The reference unit in the different sources is not the same although expressed as mg amino acid per g protein. For example ''protein'' is the sum of total anhydrous amino acids (18,24) or total nitrogen multiplied by 6.38 (23) or total nitrogen minus NPN multiplied by an unknown factor (25). To avoid this problem it seems advisable to refer the individual amino acid content to the nitrogen content to avoid confusion about the nature of the protein calculation, as suggested by the Infant formula should contain per 100 kcal an available quantity of each of the amino acids listed at least equal to that contained in the reference protein, as shown in this table.…”
Section: Amino Acid Contents Of Human Milk Protein and Requirements Fmentioning
confidence: 99%